Efeitos do treinamento f??sico combinado em modelo experimental de disfun????es cardiometab??licas associadas ?? priva????o dos horm??nios ovarianos - Conti, Filipe Fernandes (2013)
After the menopause there is an increased in the incidence of hypertension, insulin resistance, type 2 diabetes and morbidity. In other hand, aerobic exercise training has been recommended as an important therapy for the prevention and treatment of cardiometabolic disorders. Recently, resistance exercise training has been recommended as a complement to aerobic (combined training) for the treatment of cardiovascular and metabolic diseases. However, the physiological effects of this approach is not well understood. Moreover, the mechanisms involved in the possible benefits of combined exercise training have been few studied after ovarian hormone deprivation, especially in the presence of cardiometabolic disorders. Thus, the aim of this study was to evaluate the effects of exercise training combined in hypertensive ovariectomized rats submitted to fructose overload. Wistar rats and spontaneously hypertensive rats (SHR) were divided in: control (C), hypertensive (HS), hypertensive ovariectomized (HOS) and hypertensive ovariectomized submitted to fructose overload sedentary (HOFS) and trained (HOFT). Initially, the maximum load test and resistance training protocol in ladder adapted to rats were standardized. The combined exercise training was performed on a treadmill and ladder adapted to rats in alternated days. Cardiovascular function, autonomic cardiovascular modulation, metabolic and physical capacity were evaluated, as weel as the relationship of these variables with cardiac oxidative stress and inflammation. The association of hypertension and ovariecyomy induced increase in arterial pressure (AP ) (HOS: 164??5 vs. HS: 146??6 mmHg) and body weight in relation to hypertensive rats. The association of risk factors (hypertension + ovariectomy + fructose) induced an additional increase in the AP (HOFS: 174??4 mmHg), increased heart rate (HOFS: 403??12 vs. HOS: 348??16 bpm) and blood triglycerides (HOFS: 160??8 vs. HOS: 125??6.4 mg/dl), induced an impairment in the insulin sensitivity and cardiovascular autonomic modulation, oxidative stress (redox ratio of glutathione: HOFS: 8.94??0.8 vs. HOS: 13.00??1,4) and inflammation (TNF-??- HFOS: 65.8??9.9 vs. HOS: 31.7??8.6 pg/mg protein) of these animals. Moreover, the combined exercise training was able to reduce the AP (HOFTc: 158??4 mmHg) and heart rate (HOFTc: 303??5 bp), to normalize the triglyceride levels (HOFTc: 137??4.7 mg/dL), insulin sensitivity, vascular autonomic modulation. Moreover training reduced cardiac lipoperoxidation and increased antioxidant defense and redox balance of glutathione (HOFTc: 11.94 ?? 1.1) and reduced the TNF- ?? (HOFTc: 33.1??4.9 mg/dL) and increased the IL-10. The results of this study demonstrate that the association of risk factors promoted additional impairment in metabolic, cardiovascular, autonomic, inflammatory and oxidative stress parameters; and the combined exercise training was effective in reduce and/or normalize these dysfunctions.